Review: Mekanisme Aksi, Keamanan, dan Potensi Penggunaan Fenitoin untuk Terapi Epilepsi dan Pengobatan Selain Epilepsi - Ismyama, Dian Farida; Halizah, Siti Nurfitri (Jurnal Farmasi Udayana; Vol. 13, No. 2, Tahun 2024DO - 10.24843/JFU.2024.v13.i02.p03, 2025)
The antiepileptic drug phenytoin has been the first choice for the treatment of seizures since its introduction in the 1930s. The primary mechanism of phenytoin is stabilization of nerve cell membranes through inhibition of sodium channels, which reduces excessive neuronal depolarization. A computerized literature search was carried out for relevant scientific articles via Pubmed, ScienceDirect, ResearchGate and Google Scholar. A literature search was also conducted manually from the reference lists of the original articles to find additional appropriate articles. Several clinical studies summarized in this article provide insight into how phenytoin is useful for treating diseases other than epilepsy. Phenytoin is not only beneficial for seizure control, but also has neuroprotective effects in acute optic neuritis, and can be used to treat neuropathic pain, as well as post-traumatic stress disorder. However, phenytoin is a drug with a narrow therapeutic range so it must be used carefully. This understanding is important to increase the effectiveness of therapy and reduce the risks associated with phenytoin use. Keywords: antiepileptics; narrow therapeutic index; neuropathic pain; neuroprotector; phenytoin; post-traumatic stress disorder